Knowledge transfer and innovation through university-industry partnership: an integrated theoretical view. Issue 4 (2nd October 2019) - Thomas, Asha; Paul, Justin
ABSTRACT: Knowledge has vital role in the development of an economy. Universities have switched to interacting with industries like never before to achieve excellence. On the other hand, industries look forward to working and partnering with academics to a greater extent and firms are pushed to innovate by the ever-increasing competitive market forces. Fostering university/industry (U/I) relationships can pave the way for the participating firms and their subsidiaries for building social capital and portrays trust, shared goals, and network ties as the pivotal elements of the social capital theory. In this paper, we develop a theoretical model based on the integrated view that communication is the medium for building trust and strong social ties. This, in turn, can enhance the quality and effectiveness of the knowledge transferred and its utilization for inducing innovation, adapting to sophisticated technology, which in turn foster growth opportunities.